SEMANTIC TYPES AND SYNTACTIC ANALYSIS OF PARTICLES (YUKLAMA) IN THE UZBEK LANGUAGE - Saydazimova Yulduzxon Bahodir qizi (International Journal of Literature and Language Studies, 2026)
This article theoretically analyzes the concept of particles (yuklama) in Uzbek linguistics, their structural composition and semantic types. The study examines the syntactic functions of particles at the sentence and phrase level, as well as their modal pragmatic significance. The article is based solely on literature analysis and the author's personal reasoning, without any experimental or observational data.